Silikosis di kalangan perempuan pekerja tambang batu pasir: Studi kasus penyakit paru di tempat kerja - Estaurina, Edelwise Lasma; Pramudit, Nicolaus Bevan; Syahir, Raffi; Tampubolon, Yosua Rivaldo (Journal of Evidence-based Nursing and Public Health, 2024)
Exposure to fine silica dust that workers inhale while working can result in lung disease at the workplace. A related disease that can arise as a result of this exposure is silicosis. This study aims to understand the silicosis experienced by female sandstone mining workers in Budhpura Village, Rajasthan, India. The methods used are case studies and document analysis. The results show that silicosis can attack female mining workers due to a lack of health protection and weak law enforcement. The health impacts are very serious, even causing death. Pathophysiologically, silica dust that enters the lungs causes tissue damage and inflammation. To prevent this, occupational health promotion and silicosis prevention programs are needed through dust control, use of personal protective equipment, regular health checks, access to health services, as well as enforcement of regulations and protection of the rights of female workers. It is concluded that multidisciplinary cooperation and active participation by working women are needed to protect their health and rights at work.